2021
DOI: 10.1186/s12931-021-01875-w
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of pulmonary arterial hypertension and neointimal formation by kinin B1 receptor blockade

Abstract: Background This study examined whether BI113823, a novel selective kinin B1 receptor antagonist can reverse established pulmonary arterial hypertension (PAH), prevent right heart failure and death, which is critical for clinical translation. Methods Left pneumonectomized male Wistar rats were injected with monocrotaline to induce PAH. Three weeks later, when PAH was well established, the rats received daily treatment of BI113823 or vehicle for 3 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…These findings are contradictory to our observation of decreased aldosterone concentration after PAH induction. However, other authors have reported that either the transcripts or levels of natriuretic peptides were elevated in the condition of PAH [ 34 , 35 , 36 , 37 ]. These findings may provide an explanation for the surprisingly low plasma aldosterone level observed in our study simultaneously with unchanged Ang II concentration, as natriuretic peptides are inhibitors of aldosterone synthesis [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are contradictory to our observation of decreased aldosterone concentration after PAH induction. However, other authors have reported that either the transcripts or levels of natriuretic peptides were elevated in the condition of PAH [ 34 , 35 , 36 , 37 ]. These findings may provide an explanation for the surprisingly low plasma aldosterone level observed in our study simultaneously with unchanged Ang II concentration, as natriuretic peptides are inhibitors of aldosterone synthesis [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The expression and phosphorylation of VEGFR directly promoted the proliferation of PASMC cultured in vitro and indirectly promoted the proliferation of PASMC through the upregulation of MMP (matrix metalloprotein, MMP)-9. [20] Inflammatory factors such as TNF-𝛼, IL-1𝛽, [21] and CSF2 [22] were also involved in the development of PAH and were associated with the proliferation of PASMC as well as PAEC in the pulmonary vasculature. [14,16] Glia maturation factor 𝛽 (GMF𝛽) is a highly conserved amino acid polypeptide between humans and rodents, which is essential for glial cells and neuron growth and differentiation.…”
Section: Gmf𝜷 Is Involved In the Development Of Pahmentioning
confidence: 99%
“…B2R activated by bradykinin has been shown to attenuate liver damage and fibrosis development in a rat model of chronic liver injury [8]. By contrast, B1Rs are involved in diverse pathological processes, including inflammation, platelet activation, smooth muscle contraction, increased vascular permeability, oedema, pain, cytokine and chemokine release, cell proliferation, and tissue remodelling, responses that are key components of liver fibrosis [6,7,[9][10][11][12][13]. Furthermore, in contrast to the B2 receptor mediated relaxation to bradykinin, B1Rs are induced in the rat portal vein and stimulation triggers vasoconstriction via the cyclooxygenase-2 (COX-2) pathway [14].…”
Section: Introductionmentioning
confidence: 99%